Static spacers play a crucial role in the treatment of complex periprosthetic joint infections of the knee - Lunz, André; Omlor, Georg; Voss, Moritz N.; Geisbüsch, Andreas; Renkawitz, Tobias; Lehner, Burkhard (Knee surgery, sports traumatology, arthroscopy, 2024)
Purpose To determine the superior spacer design, a growing number of studies are comparing treatment results between patients having been treated with articulating and static knee spacers in the setting of two-stage revision for periprosthetic joint infection (PJI). In contrast, the primary objective of this study was to compare preoperative characteristics between patients from both spacer groups and examine whether significant differences were present prior to spacer implantation. Methods This retrospective, single-centre, cohort study examined the preoperative situation of 80 consecutive knee PJIs between 2017 and 2020. All patients underwent two-stage revision, with 35 (44%) receiving an articulating and 45 (56%) a static spacer. Results No significant differences were observed in terms of patient gender (p = 0.083), age (p = 0.666), comorbidity (p = 0.1) and preoperative clinical function (p = 0.246). Static spacers were significantly more often used in the presence of a periarticular fistula (p = 0.033), infection of a revision implant (p < 0.001), higher degree of bone loss (p < 0.001) and infection caused by a difficult-to-treat pathogen (p = 0.038). Complication and revision rates were similar for both spacer types during the interim period, while patients with articulating spacers demonstrated a superior clinical function (p < 0.001) during the interim period and after reimplantation. Conclusion Static spacers are being utilised in significantly more complex and unfavourable preoperative scenarios. Therefore, a preoperative selection bias may be at least partially accountable for any disparities observed in postoperative outcomes. To achieve the best possible results, surgeons should know and respect the distinct indications of static and articulating spacers and consequently understand and use them as complementary surgical options. Level of Evidence Level III.